2022
DOI: 10.1177/20417314221091033
|View full text |Cite
|
Sign up to set email alerts
|

Toward 3D-bioprinting of an endocrine pancreas: A building-block concept for bioartificial insulin-secreting tissue

Abstract: Three-dimensional bioprinting of an endocrine pancreas is a promising future curative treatment for patients with insulin secretion deficiency. In this study, we present an end-to-end concept from the molecular to the macroscopic level. Building-blocks for a hybrid scaffold device of hydrogel and functionalized polycaprolactone were manufactured by 3D-(bio)printing. Pseudoislet formation from INS-1 cells after bioprinting resulted in a viable and proliferative experimental model. Transcriptomics showed an upre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In silico modeling for defined architectures can predict postimplantation viability and function in vivo [ 50 ]. Defining a construct geometry in silico is a process commonly required in all additive manufacturing technologies.…”
Section: Strategies Before 3d Bioprinting: Materials Properties and B...mentioning
confidence: 99%
See 4 more Smart Citations
“…In silico modeling for defined architectures can predict postimplantation viability and function in vivo [ 50 ]. Defining a construct geometry in silico is a process commonly required in all additive manufacturing technologies.…”
Section: Strategies Before 3d Bioprinting: Materials Properties and B...mentioning
confidence: 99%
“…Defining a construct geometry in silico is a process commonly required in all additive manufacturing technologies. Computer-aided design and in silico analysis of these geometries prior to the manufacturing process itself showed the potential to improve on trial-and-error experimental approaches [ 50 , 51 ] ( Table 1 ). Previous studies on the bioprinting of insulin-producing constructs showed the potential of finite element analysis for simulation of diffusional processes of oxygen, glucose, and insulin outflow [ 50 , 51 , 52 ].…”
Section: Strategies Before 3d Bioprinting: Materials Properties and B...mentioning
confidence: 99%
See 3 more Smart Citations